110k views
0 votes
If f(x)=x/2-3 and g(x)=3x2+x-6, find (f+g)(x)

User Tasleema
by
3.9k points

2 Answers

3 votes

Answer:

Explanation:

User Manuel Spuhler
by
5.0k points
5 votes

Answer:


(f+g)(x) = 3x^2+(3x)/(2)-9\\or\\(f+g)(x) = (6x^2+3x-18)/(2)

Explanation:

We are given:


f(x)=(x)/(2)-3 \,\, and\,\, g(x) = 3x^2+x-6

We need to find
(f+g)(x)

(f+g)(x) can be found by adding f(x) and g(x)

(f+g)(x) = f(x) + g(x)


(f+g)(x) = (x)/(2)-3+(3x^2+x-6) \\(f+g)(x) = (x)/(2)-3+3x^2+x-6\\(f+g)(x) = 3x^2+(x)/(2)+x-3-6\\(f+g)(x) = 3x^2+(3x)/(2)-9\\(f+g)(x) = (6x^2+3x-18)/(2)

so, (f+g)(x) is:


(f+g)(x) = 3x^2+(3x)/(2)-9\\or\\(f+g)(x) = (6x^2+3x-18)/(2)

User Vyacheslav Loginov
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.